REMISSION POLICY FOR CORRUPTION PERPETRATORS IN THE PERSPECTIVE OF JUSTICE - Rijadi, Prof. Dr. Prasetijo; Sushanty, Vera Rimbawani; Ngaisah, Siti; Rafli, La Ode (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
Corruption is recognized as an extraordinary crime that poses significant challenges to governance and justice systems. The remission policy for corruption perpetrators often raises concerns regarding its alignment with the principles of justice, as it can be perceived as undermining the severity of corruption offenses. This research addresses the critical question of how remission policies can coexist with the values of justice, particularly in the context of Indonesia's legal framework. The primary aim of this research is to explore the legal norms surrounding the remission policy for corruption perpetrators from a justice perspective. It seeks to analyze whether the existing policies uphold the principles of fairness and justice as articulated in the Indonesian Constitution and the state ideology of Pancasila. This research employs a normative legal research methodology, utilizing secondary data such as laws and legal theories. Two key approaches are applied: a statutory approach, which interprets legal norms within existing legislation, and a philosophical approach, which delves deeply into the theoretical underpinnings of justice. The findings indicate that while remission can be viewed as a human right and a potential reward for good behavior, its application must be strictly regulated to maintain public trust and uphold justice. The research emphasizes that remission policies should be grounded in solid legal foundations and should incorporate principles of community justice to ensure that they do not compromise the fight against corruption.